‘Abd al-Karīm al-Jīlī and The Praxis of Ḥadīth - Rüdiger Lohlker (Universitas Islam Negeri Mataram, 2021)
The article provides a study of the use of ḥadīth in the works of al-Jīlī, the author of, e.g., al-Insān al-Kāmil. The article offers a fresh look on the use of ḥadīth in pre-modern Sufi writings. Esp., al-Kahf al-Raqīm a less studied work of al-Jīlī is analyzed. The study will help to precise analysis of ḥadīth in pre-modern times among Sufis. The study is not focused on the criticism of the way Sufis use ḥadīth by ḥadīth scholars. It is a reconstruction of one aspect of the thought and works of al-Jīlī as an exponent of the later school of waḥdat al-wujūd. Thus, it widens the field of ḥadīth studies to other approaches than those shared by ḥadīth scholars. It is the praxis of ḥadīth in Sufi writings that can be studied this way and not claims for authority.